Comparing Three Cognitive Biases for Alcohol Cues in Alcohol Dependence. (20th September 2016) - Wiers, Corinde E.; Gladwin, Thomas E.; Ludwig, Vera U.; Gröpper, Sonja; Stuke, Heiner; Gawron, Christiane K.; Wiers, Reinout W.; Walter, Henrik; Bermpohl, Felix
Abstract: Aims: There is accumulating evidence that automatic processes play a large role in alcohol dependence, which may be related to alcohol craving and consumption. The aim of this study is to investigate associations between cognitive biases in alcohol-dependent patients, and how these measures relate to drinking behavior. Methods: Thirty alcohol-dependent patients and 15 healthy controls (matched for age, intelligence and education; all male) completed three cognitive bias tasks: the Implicit Association Test (IAT: alcohol-approach association), Approach Avoidance Task (AAT: alcohol approach bias) and Dot Probe Task (DPT: alcohol attentional bias). Task scores were compared between groups and correlated with each other, as well as with craving scores and drinking behavior. Results: Patients with alcohol dependence showed stronger alcohol-approach associations on the IAT compared with controls, but there were no group differences for approach or attentional biases. Within the patient group, the alcohol approach bias (AAT) correlated positively with the attend-alcohol attentional bias (DPT), but negatively with alcohol-approach associations (IAT). IAT scores were positively associated with lifetime alcohol intake. Conclusions: This study demonstrates for the first time that alcohol-dependent patients have stronger alcohol-approach association scores on the IAT as compared to controls, and that this bias is associated with drinking behavior. Despite the absence of group differences for the approach and attentional biases, the positive correlation between these biases in alcoholics is in line with incentive salience models of addiction that propose that attentional and approach tendencies have a common underlying mechanism, distinct from that underlying alcohol-approach associations measured by the IAT. Short Summary: The study investigates associations between cognitive biases involving alcohol cues. Patients with alcohol dependence showed stronger alcohol-approach associations on an Implicit Association Test than controls, but there were no group differences for approach or attentional biases. Alcohol-approach and attentional bias correlated positively in the patient group.